(untitled) (Geo-Eco-Marina, 2020)
Dan Constantin Jipa, a great friend, an eminent, brilliant scientist, who has completely dedicated his life to Earth Sciences, passed away on September 28, 2020. Adieu dear friend! He worked with total dedication for over 60 years and his enthusiasm and interest in the profession did not fade even at the last moment - two months earlier, he was in the Bucegi Mountains where he had resumed his study of the Bucegi Conglomerates. We were good friends, we worked together and we supported each other to the best of our ability.